Comparative Genomic Hybridization Analysis of Yersinia enterocolitica and Yersinia pseudotuberculosis Identifies Genetic Traits to Elucidate Their Different Ecologies. (28th October 2015) - Jaakkola, Kaisa; Somervuo, Panu; Korkeala, Hannu
Abstract : Enteropathogenic Yersinia enterocolitica and Yersinia pseudotuberculosis are both etiological agents for intestinal infection known as yersiniosis, but their epidemiology and ecology bear many differences. Swine are the only known reservoir for Y. enterocolitica 4/O:3 strains, which are the most common cause of human disease, while Y. pseudotuberculosis has been isolated from a variety of sources, including vegetables and wild animals. Infections caused by Y. enterocolitica mainly originate from swine, but fresh produce has been the source for widespread Y. pseudotuberculosis outbreaks within recent decades. A comparative genomic hybridization analysis with a DNA microarray based on three Yersinia enterocolitica and four Yersinia pseudotuberculosis genomes was conducted to shed light on the genomic differences between enteropathogenic Yersinia . The hybridization results identified Y. pseudotuberculosis strains to carry operons linked with the uptake and utilization of substances not found in living animal tissues but present in soil, plants, and rotting flesh. Y. pseudotuberculosis also harbors a selection of type VI secretion systems targeting other bacteria and eukaryotic cells. These genetic traits are not found in Y. enterocolitica, and it appears that while Y. pseudotuberculosis has many tools beneficial for survival in varied environments, the Y. enterocolitica genome is more streamlined and adapted to their preferred animal reservoir.